2019
DOI: 10.1108/jd-05-2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

The concept of neutrality: a new approach

Abstract: Purpose Neutrality is a much debated value in library and information science (LIS). The “neutrality debate” is characterised by opinionated discussions in contrasting contexts. The purpose of this paper is to fill a gap in the literature by bringing these conceptions together holistically, with potential to deepen understanding of LIS neutrality. Design/methodology/approach First, a literature review identified conceptions of neutrality reported in the LIS literature. Second, seven phenomenographic intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…obtained from our HTS campaign 16 (Figure 5A and 5B) showed that merging this chemical matter may represent a viable path forward ( Figure 5C). The phenyl carboxylic acid of F2 interacts with Asn225 in a manner highly similar to the sulfonamide of 1, and provides a conformation able to access the S 4 pocket of the WBM binding site.…”
Section: Whenmentioning
confidence: 96%
See 4 more Smart Citations
“…obtained from our HTS campaign 16 (Figure 5A and 5B) showed that merging this chemical matter may represent a viable path forward ( Figure 5C). The phenyl carboxylic acid of F2 interacts with Asn225 in a manner highly similar to the sulfonamide of 1, and provides a conformation able to access the S 4 pocket of the WBM binding site.…”
Section: Whenmentioning
confidence: 96%
“…In addition to inhibiting MYC binding to WDR5 in the biochemical assays, these compounds can inhibit the WDR5-MYC interaction in cellular lysates. 16 However, these bi-aryl sulfonamide series have challenging physicochemical profiles. Multiple subseries of compounds (including acid, amide, and sulfone variants) exhibit very low F u , and many of the most potent examples contain multiple phenols that may be prone to glucuronidation or other metabolism.…”
Section: Whenmentioning
confidence: 99%
See 3 more Smart Citations